2015
DOI: 10.1371/journal.pone.0142252
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Nucleolar and Spindle-Associated Protein 1 (NUSAP1) Expression Suppresses Tumor and Cell Proliferation and Enhances Anti-Tumor Effect of Paclitaxel in Oral Squamous Cell Carcinoma

Abstract: BackgroundNucleolar and spindle-associated protein 1 (NUSAP1) is an important mitotic regulator. In addition to its crucial function in mitosis, NUSAP1 has recently received attention due to the interesting roles in carcinogenesis. The aim of this study was to reveal functional mechanisms of NUSAP1 in oral squamous cell carcinoma (OSCC).MethodsmRNA and protein expression levels of NUSAP1 in 9 OSCC-derived cells were analyzed by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
7
34
0
Order By: Relevance
“…Given its critical role in mitosis, knockdown of NUSAP1 results in decreased proliferation, cell cycle arrest in G2/M, and induction of apoptosis [26, 56, 57], as we have observed here. Transient high-level overexpression of NUSAP1 can also be toxic to cells [26, 56], limiting previous efforts to study its potential role in carcinogenesis and progression.…”
Section: Discussionsupporting
confidence: 63%
“…Given its critical role in mitosis, knockdown of NUSAP1 results in decreased proliferation, cell cycle arrest in G2/M, and induction of apoptosis [26, 56, 57], as we have observed here. Transient high-level overexpression of NUSAP1 can also be toxic to cells [26, 56], limiting previous efforts to study its potential role in carcinogenesis and progression.…”
Section: Discussionsupporting
confidence: 63%
“…Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer . And previous studies also reported downregulating NUSAP1 could enhance the susceptibility to epirubicin in invasive breast cancer and the anti‐tumour effect of paclitaxel in OSCC . In addition, high NUSAP1 expression predicted shorter survival in breast cancer, HCC, GBM, colon cancer, and glioma .…”
Section: Introductionsupporting
confidence: 56%
“…In cervical carcinoma, Li et al illuminated that NUSAP1 could promote cancer stem cell properties and epithelial‐mesenchyme transition (EMT) through activing Wnt/β‐catenin signalling, thereby accelerating cell migration and invasion. Okamoto et al revealed high NUSAP1 expression was related to more advanced T stage and inhibiting NUSAP1 resulted in the suppression of cell proliferation in Oral Squamous Cell Carcinoma (OSCC). Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Nucleolar and spindle‐associated protein 1 has been identified to play an important role in carcinogenesis. A higher expression pattern of NUSAP1 has been found in many kinds of cancers and serves as a prognostic factor, including liver cancer, breast cancer, oral squamous carcinoma, prostate cancer, pancreatic cancer, glioblastoma, and melanoma . NUSAP1 was reported to be overexpressed in bladder cancer and overexpression significantly enhanced the stemness of bladder cancer cells .…”
Section: Discussionmentioning
confidence: 99%